Near Neutral Selectionist Theories (NNST) for SARS-CoV-2 suggested by the substitution-mutation ratio (c/µ) analysis - Chun Wu; Nicholas J. Paradis (PLoS ONE, 2026)
A definitive test to measure genome-wide fitness effects of any nucleotide mutation, including translated regions ( TRs ) and untranslated regions ( UTRs ), is essential to help resolve the decades-long neutralist–selectionist debate regarding mutation-mediated species evolution. The precise boundary, composition, and abundance of nearly neutral mutations remain disputed, highlighting the need for a rigorous framework supported by empirical sequence data. Our substitution–mutation rate ratio test ( c/μ ) might provide such a framework. c/μ compares the ratio of how often mutations fix into the population (substitution rate, c ) with their expected arrival (mutation rate, µ ), which classifies each mutation type ( c/µ > 1: adaptive; c/µ = 1: neutral; c/µ < 1: deleterious). We previously showed that SARS-CoV-2 exhibits L-shaped distributions of fitness effects ( DFEs ) and a strict molecular clock, and mutation type proportions consistent only with the Near-Neutral Balanced Selectionist Theory ( NNBST ) and not with conventional molecular evolution theories. However, a theoretical explanation for incidences of non-strict clock behavior in several SARS-CoV-2 segments are not formalized. Here, we extended c/μ analysis to 49 segments of SARS-CoV-2 (26 TRs, 12 UTRs, and 10 transcriptional regulatory sequences ( TRSs )) and provide formal, mathematical frameworks for our NNBST and Near-Neutral Unbalanced Selectionist Theory ( NNUST ) to explain non-strict clock behavior. All 49 segments displayed L-shaped DFEs : 24 segments (mostly TRs ) supported molecular clocks and balanced effects of near neutral mutations, consistent with NNBST ; meanwhile, 25 segments (mostly UTRs / TRSs ) did not support molecular clocks or balancing of near neutral mutations, consistent with NNUST . Numerous violations of Selectionist Theory ( ST) , Kimura’s Neutral Theory ( KNT) , and Ohta’s Nearly Neutral Theory ( ONNT) were observed, but none for NNBST or NNUST. Together, these results support a unified Near-Neutral Selectionist Theory ( NNST ), combining neutral and selectionist perspectives to better explain the molecular evolution of SARS-CoV-2.